Association of serum secreted protein acidic and rich in cysteine-like protein 1 with metabolic measures and dyslipidemia among Chinese adults - Hu, Chunyan; Wang, Shuangyuan; Lin, Lin; Qi, Hongyan; Lin, Hong; Jia, Xiaojing; Zhu, Yuanyue; Wu, Xueyan; Li, Mian; Wang, Tiange; Zhao, Zhiyun; Xu, Min; et al. (Frontiers in Endocrinology, 2022)
Objectives: Recent studies found that secreted protein acidic and rich in cysteine-like protein 1 (Sparcl1) could inhibit lipid droplets accumulation by peroxisome proliferator-activated receptor-gamma (PPARγ) signal pathway. However, the associations of serum Sparcl1 level with lipids profiles and other metabolic phenotypes remain unknown in human population study. Methods: We determined serum Sparcl1 using sandwich enzyme-linked immunosorbent assays among 1750 adults aged 40 years and older from a community in Shanghai, China. Generalized linear regression models were used to evaluate the association between Sparcl1 and metabolic measures. Multivariable-adjusted logistic regression analyses were performed to evaluate the relationship of serum Sparcl1 with prevalent dyslipidemia. Results: With the increment of serum Sparcl1, participants tended to have lower level of triglycerides, and higher level of high-density lipoprotein cholesterol (all P for trend < 0.01). No significant associations between serum Sparcl1 and glucose, blood pressure, or body size were observed. The generalized linear regression models suggested that per standard deviation (SD) increment of serum Sparcl1 was significantly inversely associated with triglycerides (β= -0.06, P=0.02). The prevalence of dyslipidemia decreased across the sparcl1 quartiles (P for trend <0.01). After controlling the potential confounders, participants in the highest quartile of sparcl1 concentration had the lowest prevalence of dyslipidemia (odds ratio [OR], 0.69; 95% confidence interval [CI], 0.52-0.91), compared with the lowest quartile. Per SD increment of Sparcl1 was associated with 20% (OR, 0.80; 95%CI, 0.69-0.94) lower prevalence of hypertriglyceridemia and 12% (OR, 0.88; 95%CI, 0.79-0.97) lower prevalence of dyslipidemia. The association between serum Sparcl1 and dyslipidemia were generally consistent across subgroups (all P for interaction > 0.05). Conclusion: Serum Sparcl1 was significantly associated with decreased risk of prevalent dyslipidemia in Chinese population. Further studies are warranted to confirm this association.